Information theory tests critical predictions of plant defense theory for specialized metabolism - Li, Dapeng; Gaquerel, Emmanuel (Science advances, 2020)
Different plant defense theories have provided important theoretical guidance in explaining patterns in plant specialized metabolism, but their critical predictions remain to be tested. Here, we systematically explored the metabolomes of Nicotiana attenuata, from single plants to populations, as well as of closely related species, using unbiased tandem mass spectrometry (MS/MS) analyses and processed the abundances of compound spectrum-based MS features within an information theory framework to test critical predictions of optimal defense (OD) and moving target (MT) theories. Information components of plant metabolomes were consistent with the OD theory but contradicted the main prediction of the MT theory for herbivory-induced dynamics of metabolome compositions. From micro- to macroevolutionary scales, jasmonate signaling was confirmed as the master determinant of OD, while ethylene signaling provided fine-tuning for herbivore-specific responses annotated via MS/MS molecular networks. - Information theory provides a common currency for comparison of specialized metabolomes and tests defense theory predictions. - Information theory provides a common currency for comparison of specialized metabolomes and tests defense theory predictions.